Welding Fume Reduction in Flux Cored Wire Arc Welding using Nanoparticles-Shielding Gas Mixture - Phung-on, Isaratat (Science Essence Journal, 2022)
Welding fume could be harmful to welders and operators, especially to the respiratory system. In general, welding fumes could form in various types of oxides such as Fe3O4 or MnFe2O4. There have been various methods for both extracting and reducing fume formation but with some limitations. This research introduced a novel development by using a mixture of ZnO nanoparticles mixed into the shielding gas stream in the flux-cored wire arc welding process. By utilizing the photocatalytic reaction producing free electrons to neutralize the oxide metal, the fume formation would be suppressed. The system was designed as add-on equipment compiling with the existing operating parameters. Nanoparticle could reduce fume generation rate from 0.84 to 0.58 g/min (30.28%) and 0.66 to 0.46 g/min (29.65%) at shielding gas flow rate of 25 and 15 L/min, consecutively. Its robustness was applicable for %fume generation rate reduction at 29.95% and 21.33%, at welding current of 200 A and 120 A. The weld performance test conformed to the requirements of ASME BPVC.IX. Microstructure and chemical composition showed no evidence of crack and nanoparticle residue. This fume reduction utilizing nanoparticles is effective without a detrimental effect on weld performance. There is only a little adjustment during installation. Owing to its design as a refillable canister, it is convenient for the same usable duration as 1 cylinder of CO2 gas.